Characteristic analysis of received signal strength indicator from ESP8266 WiFi transceiver module - Rosli, Rafhanah Shazwani; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul (IEEE, 2018)
In recent years, the Internet of Things concept has gained an immense momentum in today’s technological world. Internet of Things connects devices efficiently which improves quality of life from various aspects. One of the most heavily used device for Internet of Things application is ESP8266 WiFi serial transceiver module. It is operating with Received Signal Strength Indicator feature. Characteristic analysis of the Received Signal Strength Indicator readings collected using ESP8266 WiFi serial transceiver module is done in this paper. The aim is to explore the future possibilities of Received Signal Strength Indicator value as a stand-alone and unique parameter to be used in various applications especially in the domain of Internet of Things. In addition, the potential of the cheap yet sophisticated ESP8266 WiFi serial transceiver module is also highlighted. The findings have shown an insight into the characteristics of Received Signal Strength Indicator readings and how it can be utilized for other different purposes. The findings have brought up a few stimulating issues that may arise from some implementation of Received Signal Strength Indicator readings. However, if solutions to the issues are to be introduced, it will thrust the Internet of Things’ technological advancements even further.